ВПЛИВ ТВОРЧОСТІ ТАРАСА ШЕВЧЕНКА ЯК ХУДОЖНИКА НА ПЕРСПЕКТИВИ ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ХУДОЖНЬОЇ ОСВІТИ НА ЧЕРКАЩИНІ - Русакова, Людмила (Збірник наукових праць Уманського державного педагогічного університету, 2020)
В статті розглядаються перспективи підвищення ефективності художньої освіти на Черкащині. Зазначено про вплив діяльності таких меценатів в галузі художньої освіти, як Н. Яшвіль та князь Голіцин. Особливу увагу звернено на художню спадщину Тараса Шевченка та її вплив на життя та художній світогляд Катерини Білокур. Автор також окреслює сучасний стан художньої освіти на Черкащині. В статье рассматриваются перспективы повышения эффективности художественного образования на Черкасщине. Указано о влиянии деятельности таких меценатов в области художественного образования, как Н. Яшвиль и князь Голицын. Особое внимание обращено на художественное наследие Тараса Шевченка и ее влияние на жизнь и художественное мировоззрение Екатерины Билокур. Автор также определяет современное состояние художественного образования на Черкасщине. The article deals with the prospects for improving efficiency of art education in Cherkasy region. It has specified on the impact of the activities of patrons in art education, as N. Iashvili and Prince Golitsyn. Particular attention is paid to the artistic legacy of Taras Shevchenko and its impact on the life and artistic vision of Catherine Bilokur. The author also outlines the current state of art education in Cherkasy region: modern universities, schools, studios, and also used main approaches. Effect of artistic works by Taras Shevchenko on modern approaches to pattern formation technology in higher art school is defined in three ways: perceptual, analytical and compositional that suggest their major types of drawing as visual simulation. The author definites also the important role of art education of Cherkasy region in the development of Ukrainian art and emphasizes the lack of coverage in the scientific educational thought of this problem, especially the future work for students.